Leptomeningeal metastasis of poorly differentiated uterine cervical adenosquamous carcinoma following reirradiation to metastatic vertebrae: A case report. Issue 19 (May 2017) - Lu, Yueh-Feng; Fong, Vai Hong; Wu, Wen-Yih; Wang, Li-Ying; Hsieh, Chen-Hsi
Abstract: Rationale: Leptomeningeal metastasis from cervical adenosquamous carcinoma is extremely rare especially after radiotherapy for vertebral metastasis. Patient concerns: A 52-year-old woman with International Federation of Gynecology and Obstetrics (FIGO) stage IIB adenosquamous carcinoma of cervix presented with bilateral lower limbs weakening after 2 courses radiotherapy to thoracic vertebral metastases. Diagnoses: Initial spine magnetic resonance imaging (MRI) showed no obvious nerve compression, and radiation myelopathy was suspected by the clinician. Progressive multifocal neurological signs developed one month after completion of spine re-irradiation. She was diagnosed with leptomeningeal metastasis by MRI and cerebrospinal fluid (CSF) study. Interventions: She received whole brain irradiation with a dose of 30 Gy in 10 fractions. Systemic chemotherapy with cisplatin (50 mg/m 2 ) and topotecan (0.75 mg/m 2 ) was administered sequentially. Outcomes: She died with progressive disease two months after the diagnosis of leptomeningeal metastases. Lessons: Poorly differentiated advanced-stage cervical adenosquamous carcinoma is an aggressive neoplasm with a worse outcome. Leptomeningeal metastasis should be included in the differential diagnosis for patients with multifocal craniospinal neurological signs. A combination of detailed neurological examinations, MRI and CSF study allowed us to establish a correct diagnosis of leptomeningeal metastasis and initiate treatment in a timely manner.